ANALYSIS OF LOAD ON PERMANENT MAGNET SYNCHRONOUS GENERATOR (PMSG) 12S8P WITH SPEED VARIATION - Wandika, Majdi; Faridah, Linda (Jurnal Informatika dan Teknik Elektro Terapan, 2025)
Abstract. This study investigates the impact of speed variation on the performance of a Permanent Magnet Synchronous Generator (PMSG) configured with 12 slots and 8 poles (12S8P) for wind energy conversion systems. PMSG has gained attention due to its high efficiency, simple design, and ability to operate effectively at low speeds, making it particularly suitable for renewable energy applications like wind turbines. Using MagNet simulation software, the performance of the PMSG was analyzed over a speed range of 1000–6000 rpm and load variations of 10–50 ohms. The results showed a maximum magnetic flux of 0.000927 Wb, while the no-load average voltage was 17.78 V at a speed of 1000 rpm. Furthermore, it was observed that voltage and current increased proportionally with speed. Optimal torque performance was achieved at a 30-ohm load at a speed of 5000 rpm, highlighting the importance of load optimization for effective energy conversion. Efficiency analysis revealed that the generator achieved its highest efficiency of 92.96% at a 10-ohm load and a speed of 5000 rpm. This study also emphasizes the influence of material properties, slot-pole design, and load conditions on generator performance. These findings provide critical insights for the design and optimization of wind turbines, particularly in regions with varying wind speeds. Moreover, this research contributes to advancing the utilization of renewable energy technologies by offering data-driven strategies for enhancing system efficiency and reliability..